Blood Coagulation and Platelet-function Parameters before and during Parenteral Administration of Medroxyprogesterone Acetate as a Contraceptive Agent - Baele, G; Vermeulen, A; Thiery, M (Thrombosis and Haemostasis, 1974)
The effects of medroxyprogesterone acetate on blood coagulation and platelet collagen aggregation were studied in nineteen women. After parenteral administration of the compound for 4 and 7 months, the activated partial thromboplastin time showed a significant decrease. The percentage of the prothrombin time test rose after 4 months, but not significantly after 7 months ; factor II decreased after 7 months of treatment. The reaction time during which no aggregation occurred after addition of a collagen suspension to a stirred platelet-rich plasma, was shorter after both 4 and 7 months of treatment. Other coagulation and platelet-function parameters were not altered. Although a trend toward hypercoagulability was detected, the changes were not the same as those reported for combined oral contraceptives.